Using colour for information retrieval in Singapore - Tan, Eng Choon. (2009)
Web users are overwhelmed by the information presented when they search for information on the Internet. Search engines and subject directories are created to assist in the search. Still, these tools are not able to reduce information overload for the users, if not eliminate. To facilitate and enhance the search, other tools or techniques should be employed as well